Real and Accrual-Based Earnings Management: Can A Qualified Auditor Detect It? - Dwi Ratmono (The Indonesian Journal of Accounting Research, 2013)
This study examines whether management of public companies in Indonesia engage real earnings management to meet earnings benchmarks. This paper documents evidence consistent with firms  committing real earnings management around earnings threshold for poor performing firms. Manager opportunistically utilize price discounts to temporarily increase sales, overproduction to report lower cost of goods sold, and reduction of discretionary expenditures to improve reported margins. Consistent with the conjecture of Roychowdhury (2006) and Cohen & Zarowin (2010) auditors find it more difficult to detect real earnings management than accrual-based earnings management. The results of this study indicate that drawing inferences about earnings management by analyzing only accrual manipulation is inappropriate. This study contributes to the accounting literature by presenting evidence on the real earnings management, which has received relatively little attention to date.